2012
DOI: 10.1002/chem.201200810
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Driven Phase Transition in a Cubic‐Phase‐Forming Binary System Composed of 4′‐n‐Docosyloxy‐3′‐nitrobiphenyl‐4‐carboxylic Acid and an Azobenzene Derivative

Abstract: Binary mixtures were prepared from an azobenzene derivative and a liquid-crystal (LC) compound that exhibits smectic C (SmC) and bicontinuous cubic (Cub(bi)) LC phases. Reversible switching between the two phases in response to UV-light irradiation was observed. This light-driven SmC-to-Cub(bi) transition is the first example showing the increased dimensionality of molecular ordering with isomerization of azobenzenes (see figure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Yamamoto and coworkers have designed novel dichiral azobenzene compounds and have found that the ( S , S )‐ and ( R , R )‐isomers show two highly ordered LC phases, SmQ L ( I 4 1 22) and SmQ H ( I 422), whereas the binary mixture shows an I 432‐Cub bi phase (a chiral version of the Im 3 m ‐Cub bi phase); in the latter mixture, a transition from the I 432‐Cub bi phase to the SmQ H phase and the emergence of optical anisotropy were photoinduced 47. Our research group has prepared Cub bi phase–forming binary mixtures containing both ANBC‐22 and an azobenzene derivative, and we have successfully observed that the mixture containing 20.1 mol % of the azobenzene derivative exhibits a reversible switching of the transition between the SmC and Cub bi phases in response to irradiation by UV light, as illustrated in Figure 6c 48. The response time was approximately ten seconds.…”
Section: Proposed Applicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Yamamoto and coworkers have designed novel dichiral azobenzene compounds and have found that the ( S , S )‐ and ( R , R )‐isomers show two highly ordered LC phases, SmQ L ( I 4 1 22) and SmQ H ( I 422), whereas the binary mixture shows an I 432‐Cub bi phase (a chiral version of the Im 3 m ‐Cub bi phase); in the latter mixture, a transition from the I 432‐Cub bi phase to the SmQ H phase and the emergence of optical anisotropy were photoinduced 47. Our research group has prepared Cub bi phase–forming binary mixtures containing both ANBC‐22 and an azobenzene derivative, and we have successfully observed that the mixture containing 20.1 mol % of the azobenzene derivative exhibits a reversible switching of the transition between the SmC and Cub bi phases in response to irradiation by UV light, as illustrated in Figure 6c 48. The response time was approximately ten seconds.…”
Section: Proposed Applicationsmentioning
confidence: 95%
“… Examples of potential applications: a) thin films of the Cub bi LC materials, applicable to 3D ion/electron conductors;11g,22,23b,24a b) molecular packing structures of the Ia 3 d ‐Cub bi and SmC phases formed by rod‐shaped molecules, as suggested from hole mobility measurements;11g and c) UV‐responsive Cub bi LC materials 48…”
Section: Proposed Applicationsmentioning
confidence: 99%
“…[5] For example, the thermotropic cubic bicontinous phases (Cub bi ) can be attractive for potential alignment-free 3D π-electronic semiconductors, [11][12][13][14] ion transportation and stimulusresponsive materials. [15] The cubic bicontinous phases, despite short-range positional correlations of neighbouring molecules, exhibit large-scale 3D periodic structure, due to the nanosegregation mechanism. [1][2][3][4][5] Initially, the 3D liquid crystalline phases were found as a lyotropic state of matter, common among water solutions of lipids and surfactants, [6,7] such phases are also frequently observed for di-block copolymers, [8] however only rarely they are formed by thermotropic mesogens.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CnTEsAz is a good candidature for a large anisotropy change of refractive index which could be provided by reversible change of rod to disc in molecular shape in an enantiotropic way. Considering the recent studies of photo-induced phase transitions on mesophase have shown an interesting evolution where one can see the more complicated mesophase order could be controlled [6], the details of mesomorphism and phase transition behavior of CnTEsAz under UV-irradiation which causes the trans-cis isomerization of azobenzene moieties to deform the mesomorphic orders should be important for further discussion toward novel optical materials. Downloaded by [Florida Atlantic University] at 17:10 16 November 2014…”
Section: Resultsmentioning
confidence: 99%